Comparison of Ventilation Volume and Airway Pressure of an Advanced Airways in Virtual Reality Ambulance Simulation (Medico Legal Update, 2020)
Background/Objectives: It is convenient to apply C-E technique during ventilation using bag-valve mask in the moving ambulance. Purpose of the study is to investigate the effective ventilation volume and airway pressure.Methods/Statistical analysis: The National Fire Service Academy conducted Virtual Reality (“VR”) based ambulance simulations from April 17, 2018 to April 28, 2018. The mean and standard deviations of mean ventilation and airway pressure were analyzed using descriptive statistics and ANOVA and SPSS software 12.0 (SPSS Ins., Chicago, IL, USA) program.Findings: When VR-based intubation was performed, the ventilation volumes were 375 ml (±30.71), 225 ml (±8.48), 324 ml (±6.56), 244 ml (±7.79), and 427 ml (±10.42) when using bag-valve mask, laryngeal mask, laryngeal tube, I-gel, and intubation, respectively. Airway pressure was 17.48 cmH2O (±0.28) from endotracheal intubation, 14.79 cmH2O (±1.51) from bag-valve mask, 13.49 cmH2O (±0.78) from laryngeal tube, 8.66 cmH2O (±0.80) from I-gel, 6.73 cmH2O (±0.53) from laryngeal mask showed airway pressure.Improvements/Applications: The present study has significance in that basic data for the method of using a professional airway are provided by adequate ventilation for each professional airway in transit.